Implementing health promotion in schools: Protocol for a realist systematic review of research and experience in the United Kingdom (UK) - Pearson, M.; Chilton, R.; Woods, H.; Wyatt, K.; Ford, T.; Abraham, Samuel; Anderson, R. (2012)
Background: School-based interventions and campaigns are used to promote health and address a wide variety of public health problems. Schools are considered to be key sites for the implementation of health promotion programmes for their potential to reach the whole population in particular age-groups and instil healthy patterns of behavior early in life. However, evidence for the effectiveness of school-based health promotion interventions is highly variable. Systematic reviews of the evidence of school-based interventions tend to be highly problem- or intervention- specific, thereby missing potential generic insights into implementation and effectiveness of such programmes across problems.Methods/design: A realist systematic review will be undertaken to explain how, why and in what circumstances schools can provide feasible settings for effective health promotion programmes in the United Kingdom (UK). The review will be conducted in two phases. Phase 1 will identify programme theories about implementation (ideas about what enables or inhibits effective health promotion to be delivered in a school setting). Phase 2 will test the programme theories so that they can be challenged, endorsed and/or refined. A Review Advisory Group of education and health professionals will be convened to help identify and choose potential programme theories, provide a 'reality check' on the clarity and explanatory strength of the mechanisms to be tested, and help shape the presentation of findings to be usable by practitioners and decision-makers. Review findings will be disseminated through liaison with decision-makers, and voluntary and professional groups in the fields of education and health.